How are the Two Most Polluted Metro-cities of India Combating Air Pollution? Way Forward after Lifting of COVID-19 Lockdown - Dipanjali Majumdar (Aerosol and Air Quality Research)
Abstract The national capital region of Delhi and Kolkata are the two metro cities in India worst affected by poor air quality. Multiple policies have been declared and implemented by the city authority in the recent past with the hope of improving the air quality of the cities and to attain the national ambient air quality standard. This study assesses that these present policies can help to reduce air pollution in these cities as much as 20% in the optimistic assessment, which may not be sufficient to attain the clean-air goal soon. During April and May 2020, the nationwide lockdown to control the pandemic of COVID-19 has unintentionally resulted in improved air quality due to force reduction at pollution emission sources. Significant pollution emitting sectors in NCR-Delhi are still not covered in current policy measures adequately. The substantial contribution of secondary aerosol formation from its precursor gases is still not addressed in any city-specific policies. The present study attempts to assess these gaps in current air pollution control policies. A way forward is indicated to empower these two polluted metro cities to attain clean air after lifting of the lockdown for the safety of the city inhabitants.